Improving undergraduate Education in Radiology - ناظم يونس سعيد (Tikrit Journal of Pharmaceutical Sciences, 2023)
Objectives: to evaluate the effectiveness of small group teaching in the radiology undergraduate training program and to assess the type of examination and the examination scores. Materials and methods: 5th year medical students in college of medicine of Hawler medical university for the academic year 2007-2008 included in this study and the effectiveness of the program assessed by a written and practical test at the end of the course. Results: 100 students enrolled in this program. The effectiveness of the program was assessed by administering a written and practical testing. Conclusion: the importance of small group teaching and objective assessment of the students are stressed and implementation of new examination scores suggested